Can CD34+CD38− lymphoblasts, as likely leukemia stem cells, be a prognostic factor in B-cell precursor acute lymphoblastic leukemia in children? - Stolpa, Weronika; Mizia-Malarz, Agnieszka; Zapała, Magdalena; Zwiernik, Bartosz (Frontiers in Pediatrics, 2023)
BACKGROUND: CD34 + CD38 -lymphoblasts as likely leukemia stem cells (LSCs) may be responsible for a worse response to treatment and may be a risk factor for recurrence in B-cell precursor acute lymphoblastic leukemia (BCP-ALL).OBJECTIVE: The study objective was to assess the prognostic role of CD34 + CD38 - lymphoblasts in bone marrow on the day of BCP-ALL diagnosis.METHODS: 115 patients with BCP-ALL, the median age of 4.5 years (range 1.5 to 17.9 years), gender: female 63 (54.8%) with BCP-ALL were enrolled; Group I (n=90) -patients with CD34 + CD38 + antigens and Group II (n=20) -patients with CD34 + CD38 -antigens on the lymphoblast surface.RESULTS: A worse response on Days 8, 15, and 33 of therapy and at the end of treatment in Group II (CD34 + CD38 -) was more often observed but these differences were not statistically significant. A significantly higher incidence of BCP-ALL recurrence was in Group II.1. In BCP-ALL in children, the presence of CD34 + CD38 -lymphoblasts at the diagnosis does not affect the first remission.2. In BCP-ALL in children, the presence of CD34 + CD38 -lymphoblasts at the diagnosis may be considered an unfavorable prognostic factor for disease recurrence.3. It is necessary to further search for prognostic factors in BCP-ALL in children.